Review on optofluidic microreactors for artificial photosynthesis - Huang, Xiaowen; Wang, Jianchun; Li, Tenghao; Wang, Jianmei; Xu, Min; Yu, Weixing; El Abed, Abdel; Zhang, Xuming (Beilstein Journal of Nanotechnology, 2018)
Artificial photosynthesis (APS) mimics natural photosynthesis (NPS) to store solar energy in chemical compounds for applications such as water splitting, CO2 fixation and coenzyme regeneration. NPS is naturally an optofluidic system since the cells (typical size 10 to 100 µm) of green plants, algae, and cyanobacteria enable light capture, biochemical and enzymatic reactions and the related material transport in a microscale, aqueous environment. The long history of evolution has equipped NPS with the remarkable merits of a large surface-area-to-volume ratio, fast small molecule diffusion and precise control of mass transfer. APS is expected to share many of the same advantages of NPS and could even provide more functionality if optofluidic technology is introduced. Recently, many studies have reported on optofluidic APS systems, but there is still a lack of an in-depth review. This article will start with a brief introduction of the physical mechanisms and will then review recent progresses in water splitting, CO2 fixation and coenzyme regeneration in optofluidic APS systems, followed by discussions on pending problems for real applications.
Keywords: artificial photosynthesis; carbon dioxide fixation; coenzyme regeneration; microfluidics; optofluidics; water splitting